2008
DOI: 10.2319/091306-370.1
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Vertebrae Anomalies—Incidental Findings on Lateral Cephalograms

Abstract: Three cases of abnormal incidental findings on lateral cephalogram are presented. These patients reported for orthodontic consultation in their adolescence. While studying the patients' cephalograms, abnormal radiographic findings were discovered in their cervical vertebrae. Because the patients were asymptomatic, early diagnosis based on these radiographic findings made the patients aware of the situations. Lifestyle changes were instituted with specialist consultation in two patients to prevent or delay the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 15 publications
3
38
0
Order By: Relevance
“…In general, the straightening of the cervical spine is orthopedically desirable and consistent with physiological straightening during growth observed in Angle class II patients. In agreement with other studies prior orthodontic correction, the children revealed occipitoatlantal dislocation, basilar impression, hyperlordosis of the cervical spine, and retroflexion of the head [3,20,21]. A persistence of those findings led to atlas displacement, descendence of the hyoid, reducement of the pharyngeal size, persistence of mouth breathing, and further retrusion of the mandible [22].…”
Section: Discussionsupporting
confidence: 89%
“…In general, the straightening of the cervical spine is orthopedically desirable and consistent with physiological straightening during growth observed in Angle class II patients. In agreement with other studies prior orthodontic correction, the children revealed occipitoatlantal dislocation, basilar impression, hyperlordosis of the cervical spine, and retroflexion of the head [3,20,21]. A persistence of those findings led to atlas displacement, descendence of the hyoid, reducement of the pharyngeal size, persistence of mouth breathing, and further retrusion of the mandible [22].…”
Section: Discussionsupporting
confidence: 89%
“…The recent literature did contain publications of case reports [9][10][11][12] and studies of sella turcica morphology. 30,31 The impact of this study's findings, along with previous findings in the literature, [1][2][3][4][5][6][7][8][9][10][11][12]22 certainly supports the position that all orthodontists who take lateral cephalograms should approach each image as a skull film and observe the entire head and neck. Then the film may be used as a source of morphometric measurements to assist in orthodontic diagnosis.…”
Section: Discussionmentioning
confidence: 69%
“…[13][14][15][16][17][18][19][20] In addition, there have been questions about orthodontists' level of responsibility in discovering incidental abnormalities on radiographs. [21][22][23][24][25][26][27][28] Thus, the frequency of pathologies on lateral cephalograms that have been discovered by practicing orthodontists could be a factor in the decision to obtain those images. Therefore, the purpose of the present study was to determine the frequency of significant pathologies on lateral cephalograms discovered by a sample of orthodontists during their careers.…”
Section: Introductionmentioning
confidence: 99%
“…Significant cervical spine pathology can be detected on the routine lateral cephalogram. 3 Since ''the eye sees what the mind knows'', one of the aims of this article is to sensitize orthodontists to ''see'' the cervical spine and be equipped to identify departures from normal anatomy (Figures 1-3). The next step is to be aware of the implications of finding these departures from the normal.…”
Section: Introductionmentioning
confidence: 99%